Effect of Temperature and Humidity on the Seasonal Phenology of Drosophila suzukii (Diptera: Drosophilidae) in Wisconsin. Issue 6 (3rd November 2018) - Guédot, Christelle; Avanesyan, Alina; Hietala-Henschell, Katie
Abstract: Drosophila suzukii (Matsumura) is an invasive pest of soft-skinned fruits that has caused significant economic damage worldwide. In this study, we focused on the seasonal abundance of D. suzukii during the early years of establishment in Wisconsin. We explored the seasonal patterns of summer and winter morphs, their reproductive output, and the effect temperature and humidity may have on their seasonal phenology. The seasonal abundance of D. suzukii during 2 yr (2014–2015) revealed that flies were detected in Wisconsin from early July to late December, with winter morphs being trapped from August through December. The adult populations trapped spanned 1 mo longer in 2015 than in 2014. The peak proportional abundance of D. suzukii in 2015 was recorded in August which was about 2 mo earlier than that in 2014. The combined factor [maximum temperature and maximum humidity] explained the most amount of variation in D. suzukii abundance consistently across the 2 yr in Wisconsin. We did not find significant differences in the fat content, number of mature eggs, proportion of females with immature eggs, or proportion of mated females between summer morph females at the beginning, summer and winter morph females during the middle, or winter morph females at the end of the collecting season in 2015. Our results build on the body of work providing a better understanding of the D. suzukii –overwintering abilities and strengthen the importance of early crop risk assessment and targeted control strategies.